A Statistical Survey on Small Scale Business Development in Nigeria - Kennedy I. Ekerikevwe; Edwin Isodje (Britain International of Exact Sciences (BIoEx) Journal, 2022)
In this paper, we examined the development of small-scale business in Nigeria. Primary data were obtained using structured questionnaires to elicit information from the study population. Data were analyzed using simple percentages and non parametric test statistic. The result showed that there is significant relationship between Entrepreneurship and development of small-scale business in Nigeria. It also shows that there is significant role of government in the development of entrepreneurship in Nigeria. The study recommends that there should be compulsory inclusion of entrepreneurship development modules in the academic programme of Nigeria institutions of learning so that entrepreneurial skills can be nurtured from the cradle. The study also recommends that government should provide technical facillities and services for Small and Medium Entreprises (SMEs) in Nigeria.